Evaluation of Settlement Distribution on Detailed Spatial Plan in Sewon District, Bantul Regency, Special Region of Yogyakarta 2018 – 2038 - Magiswari, Vabbereina Jasmineputeri; Hidayati, Iswari Nur (Faculty of Geography, Universitas Gadjah Mada, 2024)
Settlement as a place to live is one of the main needs that need to be met for the survival of human life. The need for settlement will increase along with the increase in population. The development of settlements in Sewon District. Bantul, Indonesia which is very dynamic requires monitoring to ensure that the distribution of settlements is in accordance with the spatial pattern plan that has been determined by the local government. Imagery as a remote sensing product which is then processed with the help of GIS [HV1] can be used in monitoring the distribution of settlements because it can provide more detailed information regarding land use, including settlements. This research aims to evaluate the distribution of settlements against the detailed spatial plan (RDTR) for the Sewon Urban Area (BWP) of Bantul Regency in 2018-2038. This study uses visual interpretation techniques of SPOT-7 PMS imagery in mapping existing settlement land, field surveys, and GIS processing. The research results show that mapping settlement land using imagery produces an overall accuracy of 95.20%. The settlement evaluation shows that there is a suitability of settlement land with the detailed spatial plan reaching 579.88 hectares or 87.26%, while the settlement land that is not in accordance with the detailed spatial plan is 9.62 hectares or 1.45%, and the settlement land that is temporarily not in accordance with the detailed spatial plan is 75.05 hectares or 11.29% of the total settlement area in Sewon District. Local governments must pay more attention to existing settlements with regular monitoring so that the existing settlements that are not in accordance with the detailed spatial plan will not expand.